2015
DOI: 10.1128/genomea.00267-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of an Anaerobic Ammonium-Oxidizing Bacterium, “ Candidatus Brocadia sinica”

Abstract: A draft genome sequence of an anaerobic ammonium-oxidizing (anammox) bacterium, “Candidatus Brocadia sinica,” was determined by pyrosequencing and by screening a fosmid library. A 4.07-Mb genome sequence comprising 3 contigs was assembled, in which 3,912 gene-coding regions, 47 tRNAs, and a single rrn operon were annotated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 13 publications
(10 reference statements)
3
41
0
Order By: Relevance
“…In the present study, we showed the intracellular localization of the hydroxylamine oxidoreductase (HAO)-like protein kustc0457/58, hydrazine dehydrogenase (HDH), the NO-producing HAO-like protein HOX, nitrite oxidoreductase (NXR), and hydrazine synthase (HZS) within an anammox cell. All of these proteins are encoded in all presently available anammox genomes and play key roles in anammox catabolism (1,2,(9)(10)(11)(12)(13)(14). The fact that all studied protein complexes were exclusively immunolocalized to the anammoxosome in the present study supported the hypothesis that this cell compartment was a true prokaryotic organelle with a dedicated function.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, we showed the intracellular localization of the hydroxylamine oxidoreductase (HAO)-like protein kustc0457/58, hydrazine dehydrogenase (HDH), the NO-producing HAO-like protein HOX, nitrite oxidoreductase (NXR), and hydrazine synthase (HZS) within an anammox cell. All of these proteins are encoded in all presently available anammox genomes and play key roles in anammox catabolism (1,2,(9)(10)(11)(12)(13)(14). The fact that all studied protein complexes were exclusively immunolocalized to the anammoxosome in the present study supported the hypothesis that this cell compartment was a true prokaryotic organelle with a dedicated function.…”
Section: Discussionsupporting
confidence: 76%
“…Apart from nitrite reductase, all currently available anammox genomes encode close homologs of the proteins described above (2,(9)(10)(11)(12)(13)(14), suggesting that they have the same energy metabolism as K. stuttgartiensis.…”
mentioning
confidence: 99%
“…This implies a more diverse cellular metabolism in the IFAS sludges. Of the genome assemblies of Candidatus Brocadia detected in the sludges, these samples had had very low coverage rates (4.7∼7.2%) to the reference genome Candidatus ‘Brocadia sinica’ (Oshiki et al ., ) (http://onlinelibrary.wiley.com/doi/10.1111/1462-2920.13132/suppinfo).…”
Section: Resultsmentioning
confidence: 99%
“…Kuenenia’ (Strous et al ., ; Speth et al ., ), ‘ Ca . Brocadia’ (Gori et al ., ; Oshiki et al ., ), ‘ Ca . Jettenia’ (Hira et al ., ; Hu et al ., ) and ‘ Ca .…”
Section: Physiology Of Anammox Bacteriamentioning
confidence: 99%